Teams Games Tournament Learning Model on Students Activities and Learning Outcomes at Modern Islamic Boarding School - Febriani, Husnarika; Tambunan, Efrida Pima Sari; Hasibuan, Turlan Rumaito (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2022)
This research aims to find out the influence of the Teams Games Tournament (TGT) learning model on students activities and learning outcomes of class XI at Nurul Hakim Modern Islamic Boarding School. The type of this research is a Quasy Experiment. The population in this study was all students of class XI IPA of Nurul Hakim Modern Boarding School which amounted to 60 students. The sample used was class XI IPA 1 as an experimental class of 30 students and class XI IPA 2 as a control class of 30 students. Research instruments used to find out student learning activities are using a student learning activity questionnaire and for student learning outcomes was use multiple choices test of 25 questions. Data analysis was done using hypothesis tests. The percentage of students' learning activities in the experimental class was 83.70% which was higher than the learning activities of the control class students, which was 51.50%. The average learning outcome in the experimental class model was 82.00 and in the control class was 78.00. Based on the results of the analysis of thitung > ttabel which is 3.06 > 2.00, which means that Ha is accepted, and Ho is rejected. So, it could be concluded that there is an influence of student learning activities and outcomes using the Teams Games Tournament (TGT) learning model.